Evolution of cobalt-free tungsten heavy alloys for kinetic energy penetrators. (December 2013) - Cury, Rafael; Issartel, Fabien; Joubert, Jean-Marc; Couque, Hervé
<x content-type="archive" xml:space="preserve">Abstract</x> Previous studies have demonstrated that it is possible to compensate for the absence of Co in a W–Ni–Fe liquid sintered composite alloy under industrial conditions by appropriate control of the process parameters, to achieve mechanical properties close to those of Co containing alloys. The present investigation offers an optimised description of this Co-free system, using phase analysis following long term vacuum heat treatment in a laboratory furnace, with the aim of identifying potentially brittle phases. This optimised system has been evaluated in tests with a small industrial kinetic penetrator (APFSDST CT40) against a semi-infinite target and inclined armour plate. Results show no degradation of the ballistic performance relative to conventional Co containing alloys.